Influence of groundwater levels on effective thermal conductivity of the ground and heat transfer rate of borehole heat exchangers. (5th January 2018) - Luo, Jin; Tuo, Jiasheng; Huang, Wei; Zhu, YongQiang; Jiao, YuYong; Xiang, Wei; Rohn, Joachim
Highlights: Groundwater level effects on BHE in a loess deposit area is studied by TRT. The deeper of ground level the smaller thermal conductivity of BHE is detected. The deeper of ground level the lower thermal efficiency of BHE is predicted. Effect of groundwater level change on BHE need to be considered carefully. Abstract: Effective thermal conductivity of the ground and heat transfer rate of Borehole Heat Exchanger (BHE) are two key parameters for an optimum design and planning of Ground Source Heat Pump (GSHP) systems. In general, these parameters are determined via Thermal Response Tests (TRT) in the field. Many previous studies reported that groundwater flow has positive effects on TRT to estimate ground thermal conductivity and heat transfer efficiency of BHEs. However, there still lack of data to clarify effect of groundwater levels changes on TRT. In this paper, six TRTs are conducted at two sites with different groundwater levels in a loess deposit area in 2016 and 2017. Effective thermal conductivity and borehole heat transfer rate are determined for BHEs within depth of 120 m. Results show that thermal conductivity increases remarkably with increasing groundwater level. The effective thermal conductivity of the ground is estimated to be 1.64 W/m K and 2.07 W/m K for the groundwater level of 35 m and 10 m depths. Furthermore, heat transfer rate of BHEs increases when increasing groundwater level. The findings obtained from this study indicate that groundwater level changes influence on both effective thermal conductivity of the ground and heat transfer of BHEs. These effects should be taken into account in BHE's design and installations in order to sizing the total length in the areas with seasonal groundwater level changes.